2022
DOI: 10.1080/10256016.2022.2110591
|View full text |Cite
|
Sign up to set email alerts
|

The multi-isotope biogeochemistry (S, C, N and Pb) of Hypogymnia physodes lichens: air quality approach in the Świętokrzyski National Park, Poland

Abstract: Table S2 Typical sulfur isotope compositions (δ 34 S) of major atmospheric sources. Source  34 S [‰] References Precipitations Rainfall in Poland (SO4 2− ) +3.7 Trembaczowski and Hałas (1983) Snowpack in the Świętokrzyski National Park, south-central Poland (SO4 2− ) +6.0 Michalik (2006) Precipitations in southeastern Germany (SO4 2− ) +4.0 to +5.0 Tichomirowa et al. (2007) Precipitations in northern Czech Republic (SO4 2− ) +7.0 to +8.0 Novák et al., (2001) Precipitations in southwestern Poland (SO4 2− ) +2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…water and light availability), physiological and/or biochemical processes (e.g. assimilation, metabolism and biosynthesis; Batts et al 2004 ; Beck and Mayr 2012 ; Biazrov 2012 ; Ciężka et al 2022 ; Galimov 2000 ; Hoefs 2009 ; Lee et al 2009 ), as well as other atmospheric pollutants. For instance, Batts et al ( 2004 ) reported decreasing δ 13 C with increasing pollution levels, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…water and light availability), physiological and/or biochemical processes (e.g. assimilation, metabolism and biosynthesis; Batts et al 2004 ; Beck and Mayr 2012 ; Biazrov 2012 ; Ciężka et al 2022 ; Galimov 2000 ; Hoefs 2009 ; Lee et al 2009 ), as well as other atmospheric pollutants. For instance, Batts et al ( 2004 ) reported decreasing δ 13 C with increasing pollution levels, i.e.…”
Section: Resultsmentioning
confidence: 99%